Development of Android-Based Interactive Media KaLoT on Cultural Diversity and Local Wisdom - Arin Eko Yulianto; Rahyu Setiani; Ajar Dirgantoro; Dian Septi Nur Afifah (CV. Media Digital Publikasi Indonesia, 2025)
The availability of interactive learning media determines the success of educational processes, especially in implementing the Merdeka Curriculum. This study was motivated by low learning interest (mean 53.9%) and IPAS learning outcomes (mean 68.5; below the KKTP of 75) among fourth-grade students at SD Negeri 1 Nglebo, Trenggalek, attributable to limited instructional media. This study developed the Android-based interactive learning application